AKIBAT HUKUM PENGALIHAN HAK TANGGUNGAN TANPA SEPENGETAHUAN KREDITUR DALAM TINJAUAN ASAS KESEIMBANGAN DAN ITIKAD BAIK DALAM PUTUSAN PENGADILAN - Binsneyder, Meike; Rosando, Abraham Ferry (Jurnal Hukum Bisnis Bonum Commune, 2020)
The process of buying a house through a Home Ownership Credit is always encountered problems with installment payment problems, so that the buyer is exposed to default because he does not pay the installments according to the agreement signed between the buyer and the bank. The effort taken by the buyer to avoid default in the form of a foreclosure or auction of a house is to sell to a third party. The act of the buyer transferring the ownership of the house when the credit process has not been completed to a third party raises legal problems when in the process of transfer (take over) without the knowledge of the lending Bank, such as the detention of the land deed by the Bank which is still on behalf of the first debtor. This study uses a normative approach and a case approach to review the decision No. 80 / Pdt.G / 2015 / PN.Sda on the issue of transferring credit to third parties without the knowledge of the bank, namely the National Savings Bank that provides credit. This study concludes that the court's decision to accept claims from the plaintiff (third party), although only based on evidence in the form of a stamped purchase agreement, proof of installment payments and land and building tax in a timely manner which is assessed as good faith as stated in Article 55 ( 2) Law Number 01/2011 and the provisions of Article 1338 (1) of the Civil Code is valid. Legal considerations in court decisions refer to good faith, and arguments about the application of the principle of balance in agreements that both parties should fulfill and implement the agreement, although the position of the State Savings Bank is stronger but it must be balanced with the obligation to fulfill good faith. In addition, the principle of protecting the rights of debtors in a home purchase credit agreement, in accordance with Article 4 of the UUPK, the buyer or debtor is entitled to obtain documents that are used as collateral for the duration of the credit process.Proses pembelian rumah melalui Kredit Pemilikan Rumah sepanjang waktu selalu dijumpai masalah kendala pembayaran angsuran, sehingga pihak pembeli terkena wanprestasi karena tidak membayar angsuran sesuai kesepakatan yang ditandatangani antara pihak pembeli dengan pihak bank. Upaya yang dilakukan pihak pembeli untuk menghindari wanprestasi berupa penyitaan atau pelelangan atas rumah adalah menjual pada pihak ketiga. Tindakan pembeli yang mengalihkan kepemilikan rumah saat proses kredit belum selesai ke pihak ketiga menimbulkan masalah hukum bilamana dalam proses pengalihan (take over) tanpa sepengetahuan pihak Bank pemberi kredit, seperti penahanan akta tanah oleh pihak Bank yang masih atas nama debitur pertama. Penelitian ini menggunakan pendekatan normatif dan pendekatan kasus untuk mengkaji putusan No. 80/Pdt.G/2015/PN.Sda  atas masalah pengalihan kredit  pada pihak ketiga tanpa sepengatahuan pihak bank, yaitu Bank Tabungan Negara yang memberikan kredit. Penelitian ini menyimpulkan bahwa putusan pengadilan yang menerima tuntutan dari penggugat (pihak ketiga) meskipun hanya berdasarkan bukti berupa surat perjanjian jual beli bermaterai cukup, bukti pembayaran angsuran dan pajak bumi dan bangunan secara tepat waktu yang dinilai sebagai itikat baik seperti yang tertera dalam Pasal 55 (2) UU Nomor 01/2011 dan ketentuan Pasal 1338 (1) KUH Perdata adalah sah. Pertimbangan hukum dalam putusan pengadilan mengacu pada itikad baik, dan argumentasi tentang penerapan asas keseimbangan dalam perjanjian yang semestinya kedua belah pihak memenuhi dan melaksanakan perjanjian, meskipun kedudukan pihak Bank Tabungan Negara lebih kuat namun harus diimbangi kewajiban untuk memenuhi itikad baik. Selain itu asas perlindungan hak debitur pada perjanjian kredit pembelian rumah, sesuai Pasal 4 UUPK pihak pembeli atau debitur berhak memperoleh dokumen yang dijadikan jaminan selama proses kreditnya selesai.